Pertanggungjawaban Pidana Tenaga Medis dalam Praktik Pelayanan Kesehatan Ditinjau dari Hukum Pidana Indonesia: Studi terhadap Tiga Putusan Pengadilan - Siti Nur Aprilivia; Lukman Hakim; Aly Ashgor (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study analyzes the criminal liability of medical personnel in healthcare services under Indonesian criminal law through an examination of Supreme Court Decision Number 233 K/Pid.Sus/2021, Prabumulih District Court Decision Number 120/Pid.Sus/2024/PN.Pbm and Tanjungkarang District Court Decision Number 1043/Pid.B/2023/PN.Tjk. Using a normative juridical method wit statutory and case approaches, the study finds that criminal liability may arise from violations of professional standards or from providing healthcare services without valid registration, competence, or licensing. The study recommends strengthening license verification and government supervision of healthcare facilities.